Endothelial Progenitor Cells as a Marker of Endothelial Dysfunction and Atherosclerosis in Ankylosing Spondylitis: A Cross-Sectional Study - Verma, Inderjeet; Syngle, Ashit; Krishan, Pawan; Garg, Nidhi (International Journal of Angiology, 2017)
Endothelial progenitor cells (EPCs) have reparative potential in overcoming the endothelial dysfunction and reducing cardiovascular risk. EPC depletion has been demonstrated in the setting of established atherosclerotic diseases. We evaluated whether reduced EPCs population are associated with endothelial dysfunction, subclinical atherosclerosis, and inflammatory markers in ankylosing spondylitis (AS) patients without any known traditional cardiovascular risk factor. We performed a cross-sectional study of 30 consecutive AS patients and 25 age- and sex-matched healthy controls. Patients with traditional cardiovascular risk factors were excluded. Circulating EPCs (CD34+/CD133+) were quantified by flow cytometry. The assessment of endothelial function by brachial artery flow-mediated dilatation (FMD) and ultrasound assessment of carotid intima-media thickness (CIMT) was measured in both the groups. EPCs cells were significantly (0.020 ± 0.001 vs. 0.040 ± 0.010%, p < 0.001) reduced in patients with AS compared with healthy controls. Endothelial function (7.35 ± 2.54 vs. 10.27 ± 1.73, p = 0.002), CIMT (0.63 ± 0.01 vs. 0.35 ± 0.02, p < 0.001), and inflammatory markers were also significantly (p < 0.01) altered as compared with controls. EPCs inversely correlated with tumor necrosis factor (TNF)-α and C-reactive protein (CRP) and positively correlated with endothelial function. Present study results demonstrate depleted EPC population in AS patients compared with controls. Increased level of CRP and TNF-α appears to play a key role in EPC depletion and the latter contributes to endothelial dysfunction and atherosclerosis in AS. EPC population would, therefore, represent an attractive measure of endothelial dysfunction and accelerated atherosclerosis disease associated with AS.
Keywords: ankylosing spondylitis; endothelial progenitor cells; endothelial function; carotid intima-media thickness; inflammation